THE ROLE OF SIGER INNOVATION HUB BUSINESS INCUBATOR IN THE DEVELOPMENT OF CULINARY MSMES IN BANDAR LAMPUNG - Maulana, Ibnu Arya; Agung, Maulana; Harori, M. Iqbal (Jurnal Kompetitif Bisnis, 2023)
ABSTRACT Micro, Small and Medium Enterprises (MSMEs) have an important role for the National economy. Behind such an important role for the nation MSMEs still face various problems. This study aims to find out an in-depth picture related to Siger Innovation Hub business incubator services for MSME business development in the Culinary Sector in Bandar Lampung with Reith-7S business incubator service indicators (space, shared, services, support, skill development, seed capital, and synergy). The method used in the research is a qualitative method and uses descriptive analysis. Data collection was carried out by observing, in-depth interviews, and documentation. The results of this study is the services provided by the Siger Innovation Hub to tenants include consulting services, support, skill development, seed capital, synergy.. Some services are not provided optimally by Siger Innovation Hub, such as the provision of space, and the provision of shared facilities. Keywords : Service, Business Incubator, Business Development, Micro, Small and Medium Enterprises (MSMEs)